Analisis Faktor Menurunnya Motivasi Belajar Siswa Kelas IV SD Negeri 5 Peninjoan - Dewi Yuliantari, Ni Made; Nada Kesuma, I Komang (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2024)
This study aims to identify the factors influencing the decline in learning motivation among fourth-grade students at SD Negeri 5 Peninjoan, Tembuku District, Bangli Regency. The research method used is qualitative, with data collection techniques including observation and interviews. The instruments used consist of observation and interview guidelines designed to collect data on student activities during the learning process and the perspectives of teachers and parents on student learning motivation. The results show that internal factors such as lack of interest and self-confidence, as well as external factors such as an unconducive learning environment, minimal family support, and monotonous teaching methods, contribute to the low learning motivation of students. Based on these findings, it is recommended that teachers receive training to develop more creative and interactive teaching methods, and that parental involvement in supporting children's learning at home be increased. Additionally, schools need to create a more conducive learning environment and consider the individual needs of students to enhance their learning motivation.